ANALISIS STRATEGI MICRO-LEARNING DI INSTAGRAM REELS DAN PENGARUHNYA TERHADAP LITERASI DIGITAL MAHASISWA PENDIDIKAN MASYARAKAT - Alvin Telaumbanua; Esra Haniarta Saragih; Ester Mega Rani Br Sinuhaji; Kaniwa Silvyani; Swarni V.M Sitanggang; Silvia Mariah; Sitti Subaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of micro-learning through Instagram Reels on the digital literacy of Community Education students at Universitas Negeri Medan. The phenomenon of increasing short-form video consumption has catalyzed a shift in student learning patterns, characterized by a preference for concise, visual, and highly accessible information. A quantitative approach with a correlational design was employed. Data were collected via a Likert-scale questionnaire distributed to 35 Community Education students. Data analysis techniques included normality tests, Pearson correlation, and simple linear regression. The findings reveal a correlation between micro-learning via Instagram Reels and student digital literacy, with a correlation coefficient of 0.298, categorized as a low correlation. Regression analysis yielded a significance value of 0.082 (p > 0.05), indicating that there is no significant influence between the two variables. These results suggest that the intensity of micro-learning content consumption does not directly enhance students' digital literacy skills. Digital literacy is more profoundly influenced by critical thinking abilities, information evaluation, and deep learning experiences. This research implies that micro-learning via social media is more effective as a supplementary learning tool rather than a primary source for improving digital literacy. Consequently, a more systematic integration of learning strategies is required to optimize the utilization of digital media in education.